Association Between Treatment of Secondary Hyperparathyroidism and Posttransplant Outcomes. Issue 12 (27th January 2021) - Mathur, Aarti; Sutton, Whitney; Ahn, JiYoon B.; Prescott, Jason D.; Zeiger, Martha A.; Segev, Dorry L.; McAdams-DeMarco, Mara
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Secondary hyperparathyroidism (SHPT) affects nearly all patients on maintenance dialysis therapy. SHPT treatment options have considerably evolved over the past 2 decades but vary in degree of improvement in SHPT. Therefore, we hypothesize that the risks of adverse outcomes after kidney transplantation (KT) may differ by SHPT treatment. Methods: Using the Scientific Registry of Transplant Recipients and Medicare claims data, we identified 5094 adults (age ≥18 y) treated with cinacalcet or parathyroidectomy for SHPT before receiving KT between 2007 and 2016. We quantified the association between SHPT treatment and delayed graft function and acute rejection using adjusted logistic models and tertiary hyperparathyroidism (THPT), graft failure, and death using adjusted Cox proportional hazards; we tested whether these associations differed by patient characteristics. Results: Of 5094 KT recipients who were treated for SHPT while on dialysis, 228 (4.5%) underwent parathyroidectomy, and 4866 (95.5%) received cinacalcet. There was no association between treatment of SHPT and posttransplant delayed graft function, graft failure, or death. However, compared with patients treated with cinacalcet, those treated with parathyroidectomy had a lower risk of developing THPT (adjusted hazard ratio, 0.56; 95% confidence interval, 0.35-0.89) post-KT. Furthermore, this risk differed by dialysis vintage ( P interaction  = 0.039). Among patients on maintenance dialysis therapy for ≥3 y before KT (n = 3477, 68.3%), the risk of developing THPT was lower when treated with parathyroidectomy (adjusted hazard ratio, 0.43; 95% confidence interval, 0.24-0.79). Conclusions: Parathyroidectomy should be considered as treatment for SHPT, especially in KT candidates on maintenance dialysis for ≥3 y. Additionally, patients treated with cinacalcet for SHPT should undergo close surveillance for development of tertiary hyperparathyroidism post-KT.